FLUCTUATION OF Doleschallia bisaltide LARVAE (LEPIDOPTERA: NYMPHALIDAE) ON CARICATURE-PLANT (Graptophyllum pictum) - Adi, M Bakti Samsu; Susanti, Dian; Wijaya, Nur Rahmawati (Universitas Lampung, 2021)
Fluctuation of Doleschallia bisaltide larvae (Lepidoptera: Nymphalidae) on caricature-plant (Graptophyllum pictum). Caricature-plant cultivation is often damaged due to the attack of Doleschallia bisaltide larvae. High reproduction ability of D. bisaltide is a serious problem that need to be managed, therefore it will not inflict a financial losses. This study was aimed to determine the fluctuation of D. bisaltide larval population in the caricature-plant plantation in Kalisoro, Tawangmangu. The observations were carried out with a survey method on five observation plots for seven months from March to September 2018. The data were analyzed by descriptive statistics and the Spearman rank correlation coefficient test. The results showed that the population structure was changed during the observations with the highest larval population in May. The results of Spearman rank correlation coefficient test showed significant and positive correlation between third, fourth, and fifth instars larvae with the rainfall. The control of D. bisaltide can not only depend on the presence of natural enemies, therefore control interventions were needed especially at a suitable time and environment whne the population increased.